Reproductive Health Optimization: Remarkable Benefits of Avocado Juice (Persea americana P. Mill) in Enhancing Production and Reducing Spermatozoal Abnormalities in Mice Exposed to Clove Cigarette Smoke - Kaihena, Martha; Ukratalo, Abdul M; Pangemanan, Victory O; Manery, Dodikrisno E (Universitas Karya Husada Semarang, 2024)
Background: Cigarette smoke has the potential to disrupt hormonal balance, affect spermatogenesis processes, damage spermatozoa viability, and create the presence of toxic substances in spermatozoa. On the other hand, avocados contain protein and various vitamins, such as A, B, B1, B2, E, and C, as well as other substances, such as beta-carotene, linoleic acid, lecithin, calcium, iron, pantothenic acid, potassium, phosphorus, niacin, and natural plant oils. Vitamins C and E in avocados are believed to increase the number of Leydig cells and spermatozoa. Objective: This study aims to evaluate the potential of avocado juice to improve reproductive health in mice exposed to kretek cigarette smoke. Methods: Male mice (Mus musculus) aged 2 months, weighing ±20g each, were divided into 5 randomly assigned groups: K- (control without treatment), K+ (positive control exposed to cigarette smoke), P1 (mice exposed to cigarette smoke and given avocado juice at a dose of 0.5 ml/20 g BW), P2 (mice exposed to cigarette smoke and given avocado juice at a dose of 0.7 ml/20 g BW), and P3 (mice exposed to cigarette smoke and given avocado juice at a dose of 0.9 ml/20 g BW). Cigarette smoke exposure was conducted for 14 days. Results: The results showed that regular avocado juice consumption could increase sperm production and reduce spermatozoa abnormalities in mice exposed to kretek cigarette smoke. Conclusion: The clinical implications of these findings may contribute to a better understanding of avocado juice's potential as a supplement to improve reproductive health, especially in the context of kretek cigarette smoke exposure.